Pharmacology of Proton Pump Inhibitors - Shin, Jai Moo (2008)
The gastric H,K-ATPase is the primary target for the treatment of acid-related diseases. Proton pump inhibitors (PPIs) are weak bases composed of two moieties, a substituted pyridine with a primary pK(a) of about 4.0, which allows selective accumulation in the secretory canaliculus of the parietal cell, and a benzimidazole with a second pK(a) of about 1.0. PPIs are acid-activated prodrugs that convert to sulfenic acids or sulfenamides that react covalently with one or more cysteines accessible from the luminal surface of the ATPase. Because of covalent binding, their inhibitory effects last much longer than their plasma half-life. However, the short half-life of the drug in the blood and the requirement for acid activation impair their efficacy in acid suppression, particularly at night. PPIs with longer half-life promise to improve acid suppression. All PPIs give excellent healing of peptic ulcers and produce good results in reflux esophagitis. PPIs combined with antibiotics eradicate Helicobacter pylori.